ST2249-MRSA-III: a second major recombinant methicillin-resistant Staphylococcus aureus clone causing healthcare infection in the 1970s. (May 2015) - Nimmo, G.R.; Steen, J.A.; Monecke, S.; Ehricht, R.; Slickers, P.; Thomas, J.C.; Appleton, S.; Goering, R.V.; Robinson, D.A.; Coombs, G.W.
Abstract: Typing of healthcare-associated methicillin-resistant Staphylococcus aureus (MRSA) from Australia in the 1970s revealed a novel clone, ST2249-MRSA-III (CC45), present from 1973 to 1979. This clone was present before the Australian epidemic caused by the recombinant clone, ST239-MRSA-III. This study aimed to characterize the genome of ST2249-MRSA-III to establish its relationship to other MRSA clones. DNA microarray analysis was conducted and a draft genome sequence of ST2249 was obtained. The recombinant structure of the ST2249 genome was revealed by comparisons to publicly available ST239 and ST45 genomes. Microarray analysis of genomic DNA of 13 ST2249 isolates showed gross similarities with the ST239 chromosome in a segment around the origin of replication and with ST45 for the remainder of the chromosome. Recombination breakpoints were precisely determined by the changing pattern of nucleotide polymorphisms in the genome sequence of ST2249 isolate SK1585 compared with ST239 and ST45. One breakpoint was identified to the right of oriC, between sites 1014 and 1065 of the gene D484_00045. Another was identified to the left of oriC, between sites 1185 and 1248 of D484_01632. These results indicate that ST2249 inherited approximately 35.3% of its chromosome from an ST239-like parent and 64.7% from an ST45-like parent. ST2249-MRSA-III resulted from a major recombination between parents that resemble ST239 and ST45. Although only limited Australian archival material is available, the oldest extant isolate of ST2249 predates the oldest Australian isolate of ST239 by 3 years. It is therefore plausible that these two recombinant clones were introduced into Australia separately.